Counselling for Alcohol Problems (CAP), a lay counsellor-delivered brief psychological treatment for harmful drinking in men, in primary care in India: a randomised controlled trial. Issue 10065 (14th January 2017) - Nadkarni, Abhijit; Weobong, Benedict; Weiss, Helen A; McCambridge, Jim; Bhat, Bhargav; Katti, Basavaraj; Murthy, Pratima; King, Michael; McDaid, David; Park, A-La; Wilson, G Terence; Kirkwood, Betty; et al.
Summary: Background: Although structured psychological treatments are recommended as first-line interventions for harmful drinking, only a small fraction of people globally receive these treatments because of poor access in routine primary care. We assessed the effectiveness and cost-effectiveness of Counselling for Alcohol Problems (CAP), a brief psychological treatment delivered by lay counsellors to patients with harmful drinking attending routine primary health-care settings. Methods: In this randomised controlled trial, we recruited male harmful drinkers defined by an Alcohol Use Disorders Identification Test (AUDIT) score of 12–19 who were aged 18–65 years from ten primary health centres in Goa, India. We excluded patients who needed emergency medical treatment or inpatient admission, who were unable to communicate clearly, and who were intoxicated at the time of screening. Participants were randomly allocated (1:1) by trained health assistants based at the primary health centres to enhanced usual care (EUC) alone or EUC combined with CAP, in randomly sized blocks of four to six, stratified by primary health centre, and allocation was concealed with use of sequential numbered opaque envelopes. Physicians providing EUC and those assessing outcomes were masked. Primary outcomes were remission (AUDIT score of <8) and mean daily alcohol consumed in the past 14 days, at 3 months. Secondary outcomes were the effect of drinking, disability score, days unable to work, suicide attempts, intimate partner violence, and resource use and costs of illness. Analyses were on an intention-to-treat basis. We used logistic regression analysis for remission and zero-inflated negative binomial regression analysis for alcohol consumption. We assessed serious adverse events in the per-protocol population. This trial is registered with the ISCRTN registry, number ISRCTN76465238. Findings: Between Oct 28, 2013, and July 29, 2015, we enrolled and randomly allocated 377 participants (188 [50%] to the EUC plus CAP group and 190 [50%] to the EUC alone group [one of whom was subsequently excluded because of a protocol violation]), of whom 336 (89%) completed the 3 month primary outcome assessment (164 [87%] in the EUC plus CAP group and 172 [91%] in the EUC alone group). The proportion with remission (59 [36%] of 164 in the EUC plus CAP group vs 44 [26%] of 172 in the EUC alone group; adjusted prevalence ratio 1·50 [95% CI 1·09–2·07]; p=0·01) and the proportion abstinent in the past 14 days (68 [42%] vs 31 [18%]; adjusted odds ratio 3·00 [1·76–5·13]; p<0·0001) were significantly higher in the EUC plus CAP group than in the EUC alone group, but we noted no effect on mean daily alcohol consumed in the past 14 days among those who reported drinking in this period (37·0 g [SD 44·2] vs 31·0 g [27·8]; count ratio 1·08 [0·79–1·49]; p=0·62). We noted an effect on the percentage of days abstinent in the past 14 days (adjusted mean difference [AMD] 16·0% [8·1–24·1]; p<0·0001), but no effect on the percentage of days of heavy drinking (AMD −0·4% [–5·7 to 4·9]; p=0·88), the effect of drinking (Short Inventory of Problems score AMD–0·03 [–1·93 to 1·86]; p=0.97), disability score (WHO Disability Assessment Schedule score AMD 0·62 [–0·62 to 1·87]; p=0·32), days unable to work (no days unable to work adjusted odds ratio 1·02 [0·61–1·69]; p=0.95), suicide attempts (adjusted prevalence ratio 1·8 [–2·4 to 6·0]; p=0·25), and intimate partner violence (adjusted prevalence ratio 3·0 [–10·4 to 4·4]; p=0·57). The incremental cost per additional remission was $217 (95% CI 50–1073), with an 85% chance of being cost-effective in the study setting. We noted no significant difference in the number of serious adverse events between the two groups (six [4%] in the EUC plus CAP group vs 13 [8%] in the EUC alone group; p=0·11). Interpretation: CAP delivered by lay counsellors plus EUC was better than EUC alone was for harmful drinkers in routine primary health-care settings, and might be cost-effective. CAP could be a key strategy to reduce the treatment gap for alcohol use disorders, one of the leading causes of the global burden among men worldwide. Funding: Wellcome Trust.